Tingkat Kesiapan Masyarakat Kecamatan Sayung Terhadap Rencana Pengintegrasian Pembangunan Tanggul Laut Dengan Jalan Tol Semarang-Demak - El Sifa Mega Biruni; Wakhidah Kurniawati (Teknik PWK (Perencanaan Wilayah Kota), 2021)
The plan for the construction of sea wall in Sayung Subdistrict, which was launched by the Ministry of Public Works and Public Housing, is a form of government intervention in the prevention of tidal floods in the Semarang-Demak region in the northern coastal. This development will be integrated with Semarang-Demak toll road. This decision is contradicting with the 2011-2031 Demak Urban Land-use Plan about planning of the northern Demak Regency as a Minapolitan area. According to (Larz T, 1995) the issue of regional planning is related to the inhabitants of the planning area. The readiness of the community is considered important therefore the program receives support from them. The purpose of this research is to find out how to increase the level of preparedness of the Sayung Subdistrict community towards the Semarang-Demak Toll Road development plan. This research uses the quantitative approach by using the scoring method using the Guttman scale. The result of this study is that the level of readiness of the Sayung Subdistrict community in each village is different. The lowest readiness ladder is in Sriwulan Village and Loireng Village that means no awareness as these villages on the first stage of readiness. In Purwosari Village, Sayung Village and Tambakroto Village are on the third stage of the readiness ladder that means vague awareness. Whereas Sidogemah Village and Bedono Village are on the fourth stage called pre-planning that means the most prepared villages.